Design and synthesis of novel lanthanide MOFs by unique in situ organic and inorganic reactions. (31st July 2022) - Yoon, Jung Heum; Lee, Woo Ram; Lee, Jeong Tae; Song, Jeong Hwa; Lee, Giseong; Lim, Kwang Soo
Abstract: Four novel metal–organic frameworks (MOFs), H3 O[Ln(Ox)1.5 (formate)] (Ln = Tb (1 ), Dy (2 ), Ho (3 ), Er (4 ), Ox = oxalate) were synthesized, and their structures and properties were analyzed. They were prepared by solvothermal reaction under acidic condition with structure‐directing agents (H4 dobpdc; 4, 4′‐dihydroxy‐[1, 1′‐biphenyl]‐3, 3′‐dicarboxylic acid) and the corresponding Ln metal ion(s). Single‐crystal X‐ray diffraction analysis revealed that 1 and 2 (Group I) are isostructural as Cmca space group to 3 and 4 (Group II) as Pnma space group, respectively. This result probably comes from the change in structure according to the size of the lanthanide metal. TGA showed that the framework is thermally stable up to about 300 °C for all 1–4 . Furthermore, we measured N2 adsorption at 77 K and CO2 adsorption at 195 K, and compound 2–4 had a type I adsorption isotherm graph and adsorbed CO2 . In the study, we prepared and characterized four novel Ln‐MOFs, H3 O[Ln(Ox)1.5 (formate)] (Ln = Tb (1 ), Dy (2 ), Ho (3 ), Er (4 ), Ox = oxalate) by an unique in situ synthetic method. Abstract : Four novel lanthanide metal–organic frameworks (MOFs) were synthesized, and their structures and properties were analyzed. They were prepared by solvothermal reaction under acidic condition with structure‐directing and the corresponding Ln metal ion(s). In the study, we prepared and characterized four novel Ln‐MOFs by an unique in situ synthetic method.